2011
DOI: 10.1002/ejoc.201100175
|View full text |Cite
|
Sign up to set email alerts
|

Sequential ATRA/Reductive Cyclopropanation Reactions with a Ruthenium Catalyst in the Presence of Manganese

Abstract: Atom‐transfer radical addition (ATRA) reactions of ethyl trichloroacetate, dichloromalononitrile, or diethyl 2,2‐dichloromalonate with olefins followed by dechlorination have provided functionalized cyclopropanes in one step. The RuIII complex [Cp*RuCl2(PPh3)] was used as a catalyst precursor and commercial Mn powder as reducing agent. Reactions with the less activated substrate ethyl dichloroacetate gave ATRA products with high turnover numbers but cyclopropanation was not observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 98 publications
0
11
0
Order By: Relevance
“…We have previously shown that the ATRA products derived from simple olefins can be dehalogenated with activated magnesium [16] or manganese [17] to give cyclopropanes by an intramolecular C-C coupling reaction. These results prompted us to investigate dechlorination reactions with the 1,4-addition products described above.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that the ATRA products derived from simple olefins can be dehalogenated with activated magnesium [16] or manganese [17] to give cyclopropanes by an intramolecular C-C coupling reaction. These results prompted us to investigate dechlorination reactions with the 1,4-addition products described above.…”
Section: Resultsmentioning
confidence: 99%
“…For highly activated substrates such as Cl 3 CCO 2 Et or Cl 2 C(CN) 2 , manganese should be employed as reducing agent instead of magnesium. [10] These one-pot procedures are applicable to a wide range of substrates, and the reactions can also be used to synthesize bicyclic cyclopropanes. An advantage of this method is the fact that functionalized cyclopropanes can be obtained without the utilization of potentially problematic diazo compounds.…”
Section: Sequential Reactions Involving Ru-catalyzed Atra Reactionsmentioning
confidence: 99%
“…Similar to AIBN, the additive Mg allows the catalyst loading to be reduced dramatically. [9] Recently we have shown that manganese powder can be an interesting alternative to Mg. [10] It should be pointed out that AIBN and Mg have also been used with great success in Cu-catalyzed AT RA reactions. [11] The combination of Cp*RuCl 2 (PPh 3 ) with Mg represents one of the most powerful catalytic systems for AT RA/ATRC reactions described so far.…”
Section: Reducing Agents In Ru-catalyzed Atra Reactionsmentioning
confidence: 99%
“…In a typical ATRA process, the reaction depends mainly on the radical initiation event where an alkyl radical is generated from alkyl halide, followed by the halide transfer event . Since the discovery of ATRA, great efforts have been aimed at replacing and improving the radical initiation in the system. Classically, the generation of an alkyl radical from haloalkane requires radical initiators such as organotin reagents, triethyl borane, or potentially explosive oxidants , and a high reaction temperature. Recent efforts of photoredox catalysis with Ir/Ru complexes and organic dyes have significantly expanded the potential of the ATRA reaction.…”
Section: Introductionmentioning
confidence: 99%